(1150) unloaded duplication system with repair and preventive maintenance نظام نسخ غير محمل مع الإصلاح والصيانة الوقائية - nasr aldin, youseif; abdel hafez, adel (the institute of national planning, 2018)
when we deal with the problem of finding the effect of combination of the preventive maintenance and repair to the lifetime of a two unit standby system. two policies for inspection have been considered. policy i, the operative unit undergoes inspection when the inspection time comes regardless of the state of the other unit.